If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 2x = 19 Solving -3 + 2x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 19 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 19 + 3 2x = 19 + 3 Combine like terms: 19 + 3 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 2z-31=9z+21 | | 9x+5=77 | | 15x+5=85 | | -1+2x=7 | | y^2+6y-15=0 | | 3a^2-6a+3=0 | | 3-10b=2-9 | | 18x+25=123 | | 3.5m=182 | | ln(x+8)+ln(x+2)=3 | | 14x+25=115 | | 2(b+6)+4b=376 | | 9d-27=36 | | 5x-y=13 | | -3(6x+8)=-24 | | 15*2-34x+15=0 | | 7(7c+1)-4c=13(c-2)+3 | | 2x^2-5y^2=7 | | 10-4x=193 | | 14w=91 | | 1d+(1d*4-12)=(1d*3) | | 4(x+y+z)=xyz | | 4x=7y+10 | | T-66=-55 | | 6(2x+2)=108 | | 5x^4-12x^3=0 | | 14-3(5m-12)=1-(20m+1) | | 15x^5y+35x^3y^3= | | 10+x=50 | | 2u=26 | | -(3y+3)-(-2y-6)=3 | | 5+(x+y+z+t)+10=2xyzt |